(untitled) (Journal of Philosophy Culture and Political Science, 2018)
The Republic of Kazakhstan attaches great importance to cooperation within the framework of the Shanghai Cooperation Organization (SCO). For historical, socio-economic and political reasons, Kazakhstan is strategically interested in maintaining stability and development of both multilateral and bilateral relations with the republics of Central Asia.